Current Understanding of Molecular Pathophysiology of Heart Failure With Preserved Ejection Fraction - Budde, Heidi; Hassoun, Roua; Mügge, Andreas; Kovács, Árpád; Hamdani, Nazha (Frontiers in Physiology, 2022)
Heart Failure (HF) is the most common cause of hospitalization in the Western societies. HF is a heterogeneous and complex syndrome that may result from any dysfunction of systolic or diastolic capacity. Abnormal diastolic left ventricular function with impaired relaxation and increased diastolic stiffness is characteristic of heart failure with preserved ejection fraction (HFpEF). HFpEF accounts for more than 50% of all cases of HF. The prevalence increases with age: from around 1% for those aged <55 years to >10% in those aged 70 years or over. Nearly 50% of HF patients have HFrEF and the other 50% have HFpEF/HFmrEF, mainly based on studies in hospitalized patients. The ESC Long-Term Registry, in the outpatient setting, reports that 60% have HFrEF, 24% have HFmrEF, and 16% have HFpEF. To some extent, more than 50% of HF patients are female. HFpEF is closely associated with co-morbidities, age, and gender. Epidemiological evidence suggests that HFpEF is highly represented in older obese women and proposed as 'obese female HFpEF phenotype'. While HFrEF phenotype is more a male phenotype. In addition, netabolic abnormalities and hemodynamic perturbations in obese HFpEF patients appears to have a greater impact in women then in men (1). To date, numerous clinical trials of HFpEF treatments have produced disappointing results. This outcome suggests that a “one size fits all” approach to HFpEF may be inappropriate and supports the use of tailored, personalized therapeutic strategies with specific treatments for distinct HFpEF phenotypes. The most important mediators of diastolic stiffness are the cardiomyocytes, endothelial cells, and extracellular matrix (ECM). The complex physiological signal transduction networks that respond to the dual challenges of inflammatory and oxidative stress are major factors that promote the development of HFpEF pathologies. These signalling networks contribute to the development of the diseases. Inhibition and/or attenuation of these signalling networks also delays the onset of disease. In this review, we discuss the molecular mechanisms associated with the physiological responses to inflammation and oxidative stress and emphasize the nature of the contribution of most important cells to the development of HFpEF via increased inflammation and oxidative stress.